1988
DOI: 10.1530/jrf.0.0840585
|View full text |Cite
|
Sign up to set email alerts
|

In-vitro fertilization of pig oocytes by frozen boar spermatozoa

Abstract: In Exp. 1 pig oocytes matured in vitro were used to evaluate the fertilizability in vitro of frozen epididymal (4 boars) and ejaculated (3 boars) spermatozoa that were preincubated in modified TCM-199 for 4 h at 37 degrees C. The percentages of penetrated oocytes with the frozen epididymal spermatozoa were 0-40%. In contrast, none of the oocytes were penetrated with the frozen ejaculated spermatozoa. In Exp. 2, oocytes matured in vivo were inseminated in vitro with the frozen epididymal spermatozoa that were k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
94
0
2

Year Published

1991
1991
2004
2004

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 156 publications
(102 citation statements)
references
References 7 publications
4
94
0
2
Order By: Relevance
“…Causes for this problem likely include the quality of semen at fertilization (Kim et al, 1996a;Pavlok, 2000;Sirard et al, 1993). Large variations among individual males have been noted in fertilization rates with fresh (Sirard et al, 1993) and frozen sperm (Nagai et al, 1988). Further, because the difficulty of cryopreservation of boar semen, little information is available on the relative penetration rates of fresh and frozen boar sperm from a single ejaculate.…”
Section: Introductionmentioning
confidence: 99%
“…Causes for this problem likely include the quality of semen at fertilization (Kim et al, 1996a;Pavlok, 2000;Sirard et al, 1993). Large variations among individual males have been noted in fertilization rates with fresh (Sirard et al, 1993) and frozen sperm (Nagai et al, 1988). Further, because the difficulty of cryopreservation of boar semen, little information is available on the relative penetration rates of fresh and frozen boar sperm from a single ejaculate.…”
Section: Introductionmentioning
confidence: 99%
“…66(1): [37][38][39][40][41] 2004 Sperm reach maturation during migration from the caput to the cauda of the epididymis and are retained in the cauda epididymis until ejaculation. It has been demonstrated in many species that sperm in the cauda epididymis exhibited fertility in in vitro fertilization and artificial insemination [1,4,[7][8][9]14]. For animals that die unexpectedly, transmigration of epididymal sperm, and its freeze-storage are important techniques for gamete preservation.…”
mentioning
confidence: 99%
“…It is suggested that spermatozoa in epididymides during refrigeration retain minimum ability for fertilization, which differs depending on the boar as with ejaculated spermatozoa. Boar epididymal spermatozoa can be frozen and used for IVF [2]. Normally, before freezing, they are diluted with extenders at a temperature of between 15 C and 4 C, then gradually cooled to 4 C and cryopreserved, using the same procedure as for ejaculated boar spermatozoa (reviewed by Bwanga [14]).…”
Section: Discussionmentioning
confidence: 99%
“…After thawing at 37 C, the spermatozoa were preincubated for 1 h in Medium 199 which had been adjusted to pH 7.8 [2]. A portion (10 µl) of preincubated sperm was introduced into 90 µl fertilization medium, Bracket and Oliphant solution [13] supplementing with bovine serum albumin (BSA; Fraction V, Sigma) (10 mg/ml), caffeine (Sigma) (5 mM) and casein phospho peptide (Meiji Seika Kaisha, Ltd., Tokyo, Japan) (1 mg/ml) containing 10 IVM oocytes surrounded by expanded cumulus cells.…”
Section: Ivm Ivf and Etmentioning
confidence: 99%
See 1 more Smart Citation